199k views
5 votes
5/3x+1/3x=13 1/3 + 8/3

User RobotEyes
by
5.3k points

1 Answer

3 votes

(5)/(3)x+(1)/(3)x=13(1)/(3)+(8)/(3)x

Is this correct?

Now we will add the terms of the left side


\begin{gathered} (5)/(3)x+(1)/(3)x=13(1)/(3)+(8)/(3)x \\ (6)/(3)x=13(1)/(3)+(8)/(3)x \end{gathered}

Now subtract 8/3 x from both sides


(6)/(3)x-(8)/(3)x=(40)/(3)+(8)/(3)x-(8)/(3)x
-(2)/(3)x=(40)/(3)

Cancel the denominator 3 from both sides

-2x = 40

Divide two sides by -2


(-2x)/(-2)=(40)/(-2)

x = -20

User RickWeb
by
4.5k points